Analyze the Contents of the Ideological Programs of the Satellite Network of Vesal - Alireza Dawodi; Seyed Vahid Aghili; Mohamadreza Rasouli (توسعه اجتماعی, 2019)
The purpose of the present study was to analyze the quality of contents of the ideological programs Satellite Network of Vesal. In this study, the contents of the Shiite-based ideological programs, this Satellite Network, in the third season of 2017 (October, November and August), have been dealt with using the text content analysis approach. The method of doing this is that after reviewing the Network's programs, the results of the implementation of interviews, roundtables, news and reports on the ideological programs of this network, have been converted to text send the texts have been read and coded. There are four categories in the match "Shiite superstition, the interest of the officials of the islamic republic of Iran, the injustice of Shi'a jihadism and the sectarianism or self-control of the shiites "were identified as the main categories, which, from the analysis of the categories derived from the categories, can be said that the main purpose of the satellite network is to knock the islamic state with the symbol shiite, because most of the material about the profligacy and superstition that they say is based on the islamic government of Iran have. Therefore, it is concluded that such thinking does not have a place in the Shi'a religion and, by magnifying some deviations; it can not be damaged by the principle of Shiite religion.